PENGARUH MEDIA SOSIAL INSTAGRAM AKUN @princessyahrini TERHADAP GAYA HIDUP HEDONIS PARA FOLLOWERSNYA - Monica Utari; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of the study based on the problems described above is to see the influence of social media instagram @princessyahrini account against hedonic lifestyle followersnya. The population in this study is followers account instagram @princessyahrini. Based on data that researchers found followers account instagram @princessyahrini as of March 28, 2017 as many as 17.6 million followers. The sample in this research is 100 people. In this research Model and Technique Data analysis using Simple Linear Regression Analysis approach with computer aid through SPSS programThe results of this study show that Social Media Instagram @princessyahrini Account positive effect on Hedonis Lifestyle. This is evidenced by the value of titungnya dalah 11.056 with t count significance of 0.000. The value of tcount obtained is bigger than ttable that is 11,056> 1,984. The value of coefficient of determination (R ²) is 0,593. This indicates that the independent variable Social Media Instagram @princessyahrini (X) account contributes to Hedonis Followers (Y) of 59.30% while the rest of 41.70% is influenced by other variables not included in this study.Keywords: Social Media Instagram and Hedonis Lifestyle